Synthesis and properties of poly(aryl ether sulfone)s incorporating cage and linear organosiloxane in the backbones. (7th April 2015) - Xu, Jiuduo; Zhang, Weihai; Jiang, Qiyang; Mu, Jianxin; Jiang, Zhenhua
Abstract: A series of novel copoly(aryl ether sulfone)s with polydimethyl (PDMS) and double-decker-shaped silsesquioxane (DDSQ) in the main chain were synthesized by nucleophilic substitution polymerization approach. Dihydroxy terminated eugenosiloxanes (2OH-PDMS-n) and 3, 13-di(2-methoxy-4-propylphenol)octaphenyl DDSQ (2OH-DDSQ) were synthesized. These two difunctional oligomers were used to copolymerize with 4-fluorophenyl sulfone to obtain poly(aryl ether sulfone) containing cage and linear organosiloxane (Si-PES) through one-step high-temperature solution method. Si-PES with multiple PDMS and DDSQ contents in the main chains were obtained by adjusting the molecular weight of 2OH-PDMS-n and controlling the molar ratio of 2OH-DDSQ to 2OH-PDMS-n. The dielectric constants sharply decreased as organosiloxane was introduced compared with traditional PES which the lowest value was achieved at 5% DDSQSi–PES (2.36 at 1 MHz). In addition, enhanced hydrophobic capacity peaks were obtained at 50% DDSQSi-PES surface hydrophobicity (113°) as the synergies of both linear organosiloxane and DDSQ. Furthermore, thermal and crystallization behaviors, as well as surface properties, were investigated. Graphical abstract: